2020
DOI: 10.1016/j.cels.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Cell Transcriptomics CRISPR-Activation Screen Identifies Epigenetic Regulators of the Zygotic Genome Activation Program

Abstract: Summary Zygotic genome activation (ZGA) is an essential transcriptional event in embryonic development that coincides with extensive epigenetic reprogramming. Complex manipulation techniques and maternal stores of proteins preclude large-scale functional screens for ZGA regulators within early embryos. Here, we combined pooled CRISPR activation (CRISPRa) with single-cell transcriptomics to identify regulators of ZGA-like transcription in mouse embryonic stem cells, which serve as a tractable, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 81 publications
5
63
0
Order By: Relevance
“…Elegant work has identified that the transcription factors DUX, ZSCAN4, DPPA2 and DPPA4 activate 2C specific genes by binding to MT2 LTR promoters [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Mechanistically, MERVL LTRs, therefore, regulate genes by acting as poised promoters ( Figure 2 ).…”
Section: Gene Regulation By Transposable Elements: the Newmentioning
confidence: 99%
“…Elegant work has identified that the transcription factors DUX, ZSCAN4, DPPA2 and DPPA4 activate 2C specific genes by binding to MT2 LTR promoters [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Mechanistically, MERVL LTRs, therefore, regulate genes by acting as poised promoters ( Figure 2 ).…”
Section: Gene Regulation By Transposable Elements: the Newmentioning
confidence: 99%
“…Aspects of zygotic genome activation can be studied in vitro using serum-grown mouse embryonic stem cells which contain a rare subpopulation of 2C-like cells that share features of the two-cell embryo [ 37–40 ]. Using this model, several studies have revealed an essential role for Dppa2/4 in regulating 2C-like cells and the ZGA-associated transcripts, including the Zscan4 cluster, MERVL endogenous retrovirus and LINE1 repeats, expressed in these cells [ 32 , 35 , 41 , 42 ].…”
Section: Dppa2 and Dppa4 As Epigenetic Priming Factors In Developmentmentioning
confidence: 99%
“…Dppa2/4 were initially discovered as strong inducers of the 2C-like state through a candidate-based screen where oocyte/zygotic epigenetic factors were overexpressed in mESCs and the effects on ZGA-like transcription assessed [ 32 ]. This screen approach was recently extended using CRISPR-activation coupled with a single-cell transcriptomic read out, confirming Dppa2 as a potent activator of ZGA-like transcription in ESCs [ 41 ]. Mechanistically, ChIP-seq experiments revealed that Dppa2/4 bind the Dux gene, but not other 2C-like genes or repeats, regulating its expression [ 32 , 35 , 42 ].…”
Section: Dppa2 and Dppa4 As Epigenetic Priming Factors In Developmentmentioning
confidence: 99%
“…Here, we present a protocol to perform pooled CRISPR-activation screens in mouse embryonic stem cells using 10× Genomics scRNA-seq as a readout. For complete information on the generation and use of this protocol, please refer to Alda-Catalinas et al. (2020) .…”
mentioning
confidence: 99%
“…For complete information on the generation and use of this protocol, please refer to Alda-Catalinas et al. (2020) .…”
mentioning
confidence: 99%